Pengaruh Motivasi, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Dinas Ketahanan Pangan Kota Batu - Chilman Suaidi; Ernani Hadiyati; Sugeng Mulyono (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2021)
The purpose of this study is: to prove and analyze the effect of motivation, work discipline and work environment both simultaneously and partially on the performance of employees at the Batu City Food Security Service.The sample used in this study was 40 employees in the Batu City Government Food Security Department with the questionnaire distribution method. The results of this study indicate that 1) the simultaneous influence between motivation, work discipline and work environment on employee performance at the Batu City Food Security Service, 2) there is a partial influence between motivation, work discipline and work environment on employee performance at the Food Security Service Batu City, 3) there is a dominant influence among the variables of motivation, work discipline and work environment on the performance of employees at the Batu City Food Security Service.